2006
DOI: 10.1016/j.ibiod.2006.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of the herbicide diuron by streptomycetes isolated from soil

Abstract: The diuron degrading activity of 17 streptomycete strains, obtained from agricultural and non-agricultural soils, was determined in the laboratory. All strains were identified as Streptomyces sp. by phenotypic characteristics and PCR-based assays. The strains were cultivated in liquid medium with diuron (4 mg L -1 ) at 25 1C for 15 days. Biodegradation activity was determined by high-performance liquid chromatography. The results indicated that all strains were able to degrade diuron, but to different amounts.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 32 publications
(44 reference statements)
0
26
0
6
Order By: Relevance
“…Furthermore, it has been shown that different fungi, either obtained from various culture collections or freshly isolated from agricultural soils, are capable of degrading diuron (8,20,29,52). However, neither the bacterial nor fungal diurondegrading strains have been shown conclusively to mineralize the ring structure of diuron, and with the majority of the strains potentially harmful metabolites, such as 3,4-DCA, accumulate.…”
mentioning
confidence: 99%
“…Furthermore, it has been shown that different fungi, either obtained from various culture collections or freshly isolated from agricultural soils, are capable of degrading diuron (8,20,29,52). However, neither the bacterial nor fungal diurondegrading strains have been shown conclusively to mineralize the ring structure of diuron, and with the majority of the strains potentially harmful metabolites, such as 3,4-DCA, accumulate.…”
mentioning
confidence: 99%
“…Even the most stable compounds are transformed by microorganisms to less-toxic forms (Bending et al 2007). According to Castillo et al (2006), degradation of pesticides is a multi-stage process, which is effected by a consortia of microorganisms, i.e. by enzymes produced by such microorganisms.…”
Section: Resultsmentioning
confidence: 99%
“…Diuron can cause adverse effects in the environment, and human exposure to the compound can result in irritation to the eyes, skin, and mucous membranes, as well as formation of methemoglobin in the blood and abnormalities in the liver and spleen [3,4]. It also acts as an endocrine disruptor, interfering in the processes of release, transport, and disposal of natural hormones in the body [4,5]. Analytical methods for the determination of diuron that have been reported in the literature include spectrometric [6], chromatographic [7], fluorimetric [8], capillary electrophoretic [9], and electrochemical [10] techniques.…”
Section: Introductionmentioning
confidence: 99%